Expectativas profesionales y laborales de jóvenes indígenas de Cotopaxi :Estudios de caso en los colegios intercultural bilingüe “Jatari Unancha” centro Pujilí e instituto tecnológico superior particular “Don Bosco” extensión Zumbahua - Días Cunuhay, José Manuel (2015)
This research meets the objective of identifying the professional and job expectations of indigenous youth in the Intercultural Bilingual schools "Jatari Unancha" Pujilí center, and Private Higher Technological Institute "Don Bosco" Zumbahua extension. In it issues made visible from the sociocultural context of the social actors involved it is discussed. Specifically, the research describes and analyzes, cultural, educational, social factors and mechanisms of the dynamics in the context of the institutions. An emphasis on theories that contributes to the understanding of the subject is made. An analysis of the topics of youth, indigenous youth, labor, professional and job expectations of young people on the basis of the criteria of social actors of the research is conducted. The diversity of the criteria or opinions found answers a contextual reality, however, most specifically, the sociocultural factors that influence the emergence of professional and job expectations of indigenous youth of the two institutions mentioned above. The fundamental difference is that they are two different realities as well as their professional and labor in relation to their contexts expectations.